Corporate Governance and Malaysian Politics: Theoretical Framework for Accounting Quality - Mohammed, Nor Farizal; Sanusi, Zuraidah Mohd; Alsudairi, Fahdah Sultan (International Journal of Economics and Financial Issues, 2017)
This paper reviews various theories of corporate governance in the attempt to explain the variation in the level of accounting quality in a setting with the adoption of Anglo-American corporate governance system, yet many aspects of business dealings of the setting are heavily influenced by politics. Although many prior studies examining accounting quality and corporate governance from the point of view of agency theory, the review from this paper suggests that accounting quality may also be attributed due to the presence of political influence in corporate governance structural mechanisms in firms which can be explained from resource dependency theory. The integration of the agency and resource dependency theories is appropriate in understanding what contributes to the provision of resources and effective monitoring. The theoretical contribution from this paper can be extended to future research examining quality of reporting in markets where resources allocation is highly political, particularly, in the developing countries. Keywords: Corporate governance; political influence; accounting quality JEL Classifications: M4, O16